Relationship between consumption of ultra-processed food and anthropometric parameters in school aged children - Lozano Aguilar, Verónica Mirian (2019)
Obesity and non-transmissible chronic diseases are becoming epidemic in Latin America, both in adults and children-adolescents. Objectives: To determine the relationship between consumption of ultra-processed food and anthropometric parameters in school age children of a school in El Agustino, Lima. Methods: A cross-sectional study was carried-out applying a questionnaire about consumption of ultra-processed food and measuring anthropometric parameters in school children between 9-17 years of age during November 2017. High consumption was considered (≥ 5 points) and low consumption (< 5 points). Data on sociodemographic information (age in years and gender); weight; height; body mass index (BMI); body mass index for age; height for age and abdominal perimeter were collected as well. Results: A high frequency of low consumption of ultra-processed food was found (58.18% in elementary school age and 60.5% in secondary school age children). A relationship of consumption of ultraprocessed food with weight (p=0.009), BMI (p=0.017), BMI/age (p=0.031) and abdominal perimeter (p=0.033) was found among elementary school age children. Among secondary school age students, a relationship between age and low consumption of ultra-processed food was found (p=0,008). Conclusions: Among elementary age students a relationship of consumption of ultra-processed food and weight, BMI, BMI/age and abdominal perimeter was found, while only a relationship with age was found among secondary age students.